The Response of Maize Lines to Foliar Fertilizing - Milan Brankov; Milena Simić; Željko Dolijanović; Miloš Rajković; Violeta Mandić; Vesna Dragičević (Agriculture, 2020)
The objective of this study was to evaluate the impact of two foliar fertilizers applied on five maize (Zea mays L.) lines. Fertilizers were applied at different growth stages of maize, during three consecutive years (2010–2012) at the experimental field of the Maize Research Institute “Zemun Polje”, Serbia. Maize growth parameters such as fresh matter, height, leaf area and grain yield were recorded. Foliar fertilizer with amino acids (FAA) was more advantageous to maize plants compared to fertilizer containing phosphorus (FP) as a main component. Applied FAA has shown positive effects by increasing fresh matter, leaf area index, and plant height in all three years. In 2012, due to unfavorable meteorological conditions, grain yield and harvest index were very low, compared to the previous two years, although, positive effects on morphological traits were observed 21 days after treatments (DAT), as well as in the anthesis stage. The best results of 30% of grain yield and harvest index increase were recorded in line L1 in 2010 and 2011. The same line had an increase of more than 40% of fresh matter and leaf area on average for all three years. The positive effects that have been noticed in this research could recommend foliar fertilizing with fertilizer containing N in a form of an amino acids complex.